European Parliament's Political Groups in Turbulent Times - Ahrens, Petra; Elomäki, Anna; Kantola, Johanna (Palgrave Studies in European Union Politics, 2022)
This open access book provides the first ever authoritative collection of scholarly insights, based upon original research, into the political groups of the EP tackling the fundamental changes since the Lisbon Treaty and the upsurge of radical right parties. It analyses political groups and their importance from multiple perspectives critically assessing their role and significance in EU politics. Each chapter is authored by leading scholars in the field, working on key topics in relation to political groups: political group formation and function, their role in parliamentary and EU policy-making, the way that Eurosceptic MEPs influence (or not) the Parliament, and the nature and form of interactions with external actors. In doing so, each chapter opens hitherto unexplored 'black boxes' in the political work of the EP, such as the internal practices of, and power relations within the political groups, and informal arenas of intra-group decision-making.